If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + -92 = 7 Reorder the terms: -92 + f = 7 Solving -92 + f = 7 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '92' to each side of the equation. -92 + 92 + f = 7 + 92 Combine like terms: -92 + 92 = 0 0 + f = 7 + 92 f = 7 + 92 Combine like terms: 7 + 92 = 99 f = 99 Simplifying f = 99
| p+0.5=-0.9 | | 4=w+-13 | | f-7=2 | | 3x-5+4x+10+x-5=180 | | br-bs= | | -9=9+v | | 4x=2x+4y | | 61=c+54 | | a/.5=2 | | v+-10=-5 | | 17=u-16 | | Y-4=-1x+3 | | 59=5y-11 | | 180=30+123+b | | 9=n+4 | | 2x+4+6X=-68 | | 9=2+4 | | 180=(16x-3)+45 | | 38=6x+6x-10 | | 29=6 | | -11=p-17 | | 4x-6+5x=57 | | 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form |